2007
DOI: 10.1080/00103620601174643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liming on the Plant Availability and Distribution of Zinc and Copper among Soil Fractions

Abstract: Information on the redistribution of applied micronutrients into different fractions as a result of lime application is important to predict plant accumulation of nutrients and to select appropriate chemical extraction procedures for evaluation of micronutrient availability. The present work was carried out to study the influence of liming on the availability and redistribution of zinc (Zn) and copper (Cu) among soil fractions. Additionally, the effect of liming was evaluated on the recovery of these micronutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…The differential extraction of Zn by the extractants is because of their varied chemical nature. Nascimento et al (2007) reported that out of DTPA, Mehlich 1 and Mehlich 3 extractants, Mehlich 3 was the most efficient extractant to predict the plant accumulation of Zn in acid soils of Brazil whereas DTPA was found the most efficient for limed soils. Gartley et al (2002) compared Mehlich 1, Mehlich 3 and 0.1 M HCl for their Zn extractable capacity from soil and found best fits for each extractant combination as indicated by high R 2 value.…”
Section: Relationship Of Extractable Zn Amongst Themselves and With Tmentioning
confidence: 96%
“…The differential extraction of Zn by the extractants is because of their varied chemical nature. Nascimento et al (2007) reported that out of DTPA, Mehlich 1 and Mehlich 3 extractants, Mehlich 3 was the most efficient extractant to predict the plant accumulation of Zn in acid soils of Brazil whereas DTPA was found the most efficient for limed soils. Gartley et al (2002) compared Mehlich 1, Mehlich 3 and 0.1 M HCl for their Zn extractable capacity from soil and found best fits for each extractant combination as indicated by high R 2 value.…”
Section: Relationship Of Extractable Zn Amongst Themselves and With Tmentioning
confidence: 96%
“…This shows that although the increase of soil pH provided by liming decreases the bioavailable fractions and increases the adsorption (Nascimento et al, 2007) by redistributing these elements into more stable fractions with higher binding energy (Brunetto et al 2014), the methods used in routine laboratories to evaluate the availability of these micronutrients are not always able to detect these changes (Fonseca et al, 2010). On the other hand, liming causes greater mineralization of organic matter by improving the soil chemical condition for microorganisms (Ernani et al, 2002), which can provide part of the micronutrients that were present in the soil organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…Although some forage species are rustic and adapted to tropical acid soils (Bandinelli et al, 2005), pastures generally do not reach the maximum yield potential due to absence of agronomic techniques such as liming and fertilization. Micronutrients copper (Cu), zinc (Zn) and boron (B) are adsorbed to soil components (organic matter, oxides, clay minerals) and only a small amount is available to the plants (Nascimento et al, 2007;Garcia et al, 2008;Brunetto et al, 2014). Normally, soils with high clay and organic matter content at their natural pH present reasonable reserves of these micronutrients that are in equilibrium with the soil solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0.1 mol L 21 HCl and DTPA-TEA solutions extracted more Zn at 0-0.05 and 0.05-0.10 m deep, respectively, as a consequence of surface re-liming (Table 2). Decreases in the availability Zn have often been observed, mainly in the exchangeable fraction, as a consequence of soil pH increase through liming (Fageria, Baligar, and Clark 2002;Nascimento et al 2007). Our experiment, however, was carried out in field conditions, whereas most of the studies were conducted in pots under greenhouse conditions.…”
Section: Soil Reaction and Zinc Availability For Different Extractantsmentioning
confidence: 98%